Artikel The Effect of Teaching Certification on the Performance of Physical Education Sports and Health Teacher in Paser Regency, East Kalimantan - Pratama, Deska Cahya; Sulaiman, Sulaiman; Soegiyanto, Soegiyanto (Journal of Physical Education and Sports, 2021)
This study aims to analyze the performance of certified physical education, sports, and health teachers. Method used the case study design, the data collection used interview, observation, and documentation. Sources of data consist of school principals and certified physical education teachers in Paser Regency, East Kalimantan Province. The sources of data were obtained from school principals and certified Physical Education in Sports and Health (PESH) teacher. Data were obtained from a sample of 9 schools, 4 PESH certified teachers, and 9 principals in Paser Regency. Results of study on the performance of certified PESH teachers were reviewed with 5 indicators, quality of work, the accuracy of work, initiative, ability of work, and good communication shown in the results of the Employee Performance Target assessment which increased. The certified PESH teachers are teachers who have good abilities because they have passed the test process. The ability that has been proven to have an influence on the performance of teachers, it is characterized by the quality of work, accuracy of work, initiative, ability of work, and good communication. Results of study on the performance of PESH certified teachers were reviewed with five indicators, namely work quality, work accuracy, initiative, work ability, and good communication showed significant differences, which are marked by the exceeding of these five indicators. Conclusion this study, there are positive effect of certification on the performance of PESH teachers which is characterized by indicators of work quality, work accuracy, initiative, work ability, and good communication.